Faktor-Faktor Yang Mempengaruhi Produksi Padi di Kecamatan Paleleh Kabupaten Buol - Lailu, Adinda; Canon, Syarwani; Akib, Fitri Hadi Yulia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aimed to analyze the effect of land area, capital, labor and technology dummy on rice production in Paleleh sub-district, Buol district. The primary data used in this study was sourced from 92 respondents. This study used Multiple Linear Regression Analysis.The results of this study indicate that land area has a positive and significant effect on rice production in Paleleh Sub-district, Buol Regency, implying that any increase in land area can increase rice production. This condition can be explained in real terms. Conversely, capital has a positive and insignificant effect on rice production in Paleleh Sub-district, Buol Regency, indicating that any increase or decrease in capital cannot increase or decrease rice production. This can be explained significantly. 3). Labour positively and significantly affects rice production in Paleleh Sub-district, Buol Regency, indicating that any increase in labor can increase rice production. This can be explained significantly. 4). Technology dummy novely and affects rice production in Paleleh Sub-district, Buol Belu??c increase in technology dummy can decrease rice po significantly. significantly Mocating that any can be explained.